2014
DOI: 10.1007/s00787-014-0597-9
|View full text |Cite
|
Sign up to set email alerts
|

Minor neurodevelopmental impairments are associated with increased occurrence of ADHD symptoms in children born extremely preterm

Abstract: ADHD is more common in children born preterm than at term. The purpose of the study was to examine if, and to what extent, ADHD symptoms are associated with minor neurodevelopmental impairments (NDI) in extremely preterm children. In a national population-based cohort with gestational age 22-27 weeks or birth weight <1,000 g assessed at 5 years of age, scores on Yale Children's Inventory (YCI) scales (seven scales) were related to normal functions vs. NDI defined as mild impairments in cognitive function (IQ 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
1
23
1
1
Order By: Relevance
“…The incidence of moderate-late preterm birth (32-37 weeks of gestation) has significantly increased in developed nations over the past two decades (Frey and Klebanoff, 2016;Ananth and Vintzileos, 2006;Beck et al, 2010;Martin et al, 2010). In line with this rise, it is also becoming increasingly evident that survivors of moderate-late preterm birth are at an increased risk of neurodevelopmental disorders in childhood and adolescence (Cheong and Doyle, 2012;Chyi et al, 2008; were more likely to be diagnosed with anxiety disorder than females born at term (Elgen et al, 2014). In a large Danish cohort of 2-18 year old children, preterm birth at 34-36 weeks of gestation was associated with an 80% increased risk of being diagnosed with hyperkinetic disorder (characterized by inattention, hyperactivity, and impulsivity) compared to children born after 37 weeks' gestation, interestingly 90% of affected children were male (Linnet et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of moderate-late preterm birth (32-37 weeks of gestation) has significantly increased in developed nations over the past two decades (Frey and Klebanoff, 2016;Ananth and Vintzileos, 2006;Beck et al, 2010;Martin et al, 2010). In line with this rise, it is also becoming increasingly evident that survivors of moderate-late preterm birth are at an increased risk of neurodevelopmental disorders in childhood and adolescence (Cheong and Doyle, 2012;Chyi et al, 2008; were more likely to be diagnosed with anxiety disorder than females born at term (Elgen et al, 2014). In a large Danish cohort of 2-18 year old children, preterm birth at 34-36 weeks of gestation was associated with an 80% increased risk of being diagnosed with hyperkinetic disorder (characterized by inattention, hyperactivity, and impulsivity) compared to children born after 37 weeks' gestation, interestingly 90% of affected children were male (Linnet et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Along with anxiety, attention deficit hyperactivity disorder (or ADHD) is the most commonly diagnosed neurodevelopmental disorder in school‐aged ex‐preterm children (Lindstrom et al, 2011; Linnet et al, 2006). ADHD is characterized by a deficit in behavioural inhibition, inattention, impulsivity and social difficulties, and in a cohort of children at 5 years old it was more commonly diagnosed in males following preterm birth compared to term birth (Elgen et al, 2014). In the same cohort, preterm females were more likely to be diagnosed with anxiety disorder than females born at term (Elgen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Such disabilities are strongly associated with mental health problems irrespective of being born premature. [16][17][18][19] Assessment of mental health in children with severe NDDs, such as intellectual disability (ID) (IQ <70), requires appropriately validated tools, 18,20,21 but most EP/ELBW studies have included children with severe NDDs without using instruments validated for this subgroup. [1][2][3][4][5][6][7][8][9][10][11][12][22][23][24] In subanalyses, some studies have found increased risk of mental health problems in EP/ELBW children without severe NDDs, but frequencies and effect sizes were not reported.…”
mentioning
confidence: 99%
“…Psychiatric risk in extremely preterm children has been found to be higher in those with coexisting neurodevelopmental disabilities (35), although neurodevelopmental disabilities have been also associated with psychopathology irrespective of very preterm birth (36). In this study, up to two thirds of children with clinically significant ADHD-inattentive symptoms had comorbid neurodevelopmental disabilities, as did one quarter of those with clinically significant ADHD-hyperactive/impulsive symptoms.…”
Section: Discussionmentioning
confidence: 99%